Public Sphere of Hannah Arendt (Review of Hannah Arendt's Thoughts) - Ibnu, Cian; Ikha Rahardiantini; Lili Sartika; Masyitah Novia Yanti; Aulia Chintara Wanda (Social Impact Journal, 2024)
This study aims to examine the concept of public sphere according to Hannah Arendt. The study of public sphere uses a content analysis approach to Hannah Arendt's thoughts and works. This analysis is based on qualitative data content analysis, namely data sourced from written works, both direct works and works about her. The research strategy used is a narrative content analysis strategy, using in-depth interviews with figures who understand the thoughts being studied. The results of the study found that the concept of public sphere according to Hannah Arendt was built by a unique element, namely Vita Acktiva. Through this concept, humans are defined as creatures who are always active. Both mental and sensory activities. Whether it is inner action or real action. Human life that only thinks, wants and considers is included in mental actions or inner actions of humans. While the life of human activity working, creating and speaking is included in real action. An action or behavior that is able to build a world together with fellow humans.